Enabling Conditions for Bioenergy Finance and Investment in Colombia. - OECD. (Paris : Organization for Economic Cooperation & Development, 2022)
Colombia has set forth a number of important policy strategies to achieve its clean energy ambitions, including the 2018 Green Growth Policy, the 2019 National Circular Economy Strategy and the 2022 Energy Transition Policy. These strategies all note the role sustainable bioenergy and waste-to-energy can play in supporting decarbonisation objectives. This report looks at the enabling conditions to encourage development of these clean energy solutions and mobilise the necessary finance and investment.
Lessons learned and implications for opportunities moving forward -- India: foreign investment for paddy straw to biogas in Punjab -- The Verbio biogas project -- Financing biogas development -- Lessons learned and implications for the Colombia context -- Turkey: biogas production from livestock manure -- The experience of Energrom Energy in developing biogas capacity -- An enabling policy environment for bioenergy market development -- Lessons learned and implications for the Colombian context.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Clean energy investment; Colombia; Electronic books